An automated control system for pilot-scale biohydrogen production: Design, operation and validation. (4th February 2020) - Lu, Chaoyang; Zhang, Huan; Zhang, Quanguo; Chu, Chen-yeon; Tahir, Nadeem; Ge, Xumeng; Jing, Yanyan; Hu, Jianjun; Li, Yameng; Zhang, Yang; Zhang, Tian
Abstract: Studying biohydrogen production via sequential dark- and photo-fermentation at the pilot-scale is of practical significance. In this study, an 11 m 3 pilot-scale bioreactor was used to investigate biohydrogen production via dark- and photo-fermentation. Solar energy was used to provide heat, illumination, and power for the bioreactor, thereby reducing biohydrogen production cost greatly and indirectly reducing carbon emissions. Gas production rates were 96.30 mol/m 3 -d and 224.68 mol/m 3 -d via dark- and photo-fermentation, respectively. The pH values and oxidation-reduction potential varied from 5.13 to 5.92 and −382 mV to −490 mV, respectively. Low relative average deviations between on-line and off-line data show efficient stability. This automated reactor system could potentially contribute industrialization of biohydrogen production. Graphical abstract: Image 1 Highlights: A pilot-scale dark- and photo-fermentation bioreactor system was designed. Sun-light was used as a primary energy source for heating and illumination. Operation parameters were on-line monitored and automatically controlled. The automated control system has proven to be stable and reliable.